2018
DOI: 10.1002/pbc.27400
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of HLH‐2004 criteria in distinguishing malignancy‐associated hemophagocytic lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is characterized by dysregulated immune activation.  Primary HLH involves hereditary deficits in cytotoxic lymphocytes while secondary HLH is triggered by extrinsic factors. The HLH‐2004 criteria are widely used for clinical diagnosis, yet their specificity for HLH or their ability to differentiate primary from secondary disease is unclear, potentially leading to inappropriate treatment. We describe several cases where fulfillment of HLH‐2004 criteria obscured the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 14 publications
0
43
0
2
Order By: Relevance
“…Lymphoma deserves special mention as it is the most common malignancy associated with HLH at its initial presentation. Because of the difficulty of distinguishing lymphoma from F‐HLH or R‐HLH, thorough imaging and aggressive biopsy, often guided by PET‐CT, should be pursued or at least considered before starting corticosteroids and other therapies that may obscure diagnosis . Malignancy may present with HLH at all ages (including infancy), but is increasingly likely at older ages, and is associated with perhaps a majority of cases in adults .…”
Section: Typical and Unusual Hlh Presentation Phenotypesmentioning
confidence: 99%
“…Lymphoma deserves special mention as it is the most common malignancy associated with HLH at its initial presentation. Because of the difficulty of distinguishing lymphoma from F‐HLH or R‐HLH, thorough imaging and aggressive biopsy, often guided by PET‐CT, should be pursued or at least considered before starting corticosteroids and other therapies that may obscure diagnosis . Malignancy may present with HLH at all ages (including infancy), but is increasingly likely at older ages, and is associated with perhaps a majority of cases in adults .…”
Section: Typical and Unusual Hlh Presentation Phenotypesmentioning
confidence: 99%
“…1,2 HLH is a syndromic diagnosis made by meeting at least five of eight of the HLH-2004 diagnostic criteria, although this is not 100% specific. 3 Syntaxin 11 (STX11) is crucial for cytotoxic granule exocytosis. Mutations in the STX11 gene lead to failure of cytotoxic lymphocyte degranulation and are classified as FHL type 4 (FHL4).…”
Section: Stx11-deficient Familial Hemophagocytic Lymphohistiocytosis mentioning
confidence: 99%
“…4-6 FHL4 often presents later (postinfancy) than other types of FHL; however, additional phenotypic features of this supposed milder disease have otherwise not been described. [7][8][9][10][11] A previously healthy 18-month-old male child with no relevant family history presented with 10 days of fever and diarrhea, and was found to have pancytopenia (WBC: 4500 cells per mm 3 ; ANC: 270 per mm 3 ; hemoglobin: 6.8 g/dL; platelets: 19 000 per mm 3 Two weeks later, the patient developed recurrent pancytopenia, febrile neutropenia, and enlarging splenomegaly compared to discharge. He was readmitted with a presumed ALPS flare and given steroids and mycophenolate mofetil (MMF).…”
Section: Stx11-deficient Familial Hemophagocytic Lymphohistiocytosis mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, data have been emerging which call into question the specificity and relevance of several of the HLH-2004 criteria among adults with suspected secondary HLH. 5,6 Much of these data have focused on the criterion of serum ferritin, a non-specific marker of inflammation which, when markedly abnormal, is often a primary driver of HLH workups among hospitalized patients. 7,8 Studies examining serum ferritin thresholds >3000 ng/mL, 4000 ng/mL, 10 000 ng/mL, and 50 000 ng/mL have demonstrated that hyperferritinemia lacks specificity for HLH.…”
Section: Introductionmentioning
confidence: 99%